BATASAN KETAATAN ISTRI TERHADAP SUAMI DALAM MENGGAPAI RUMAH TANGGA SAKINAH MAWADDAH WA RAHMAH DALAM PANDANGAN ISLAM - Mudaí, Syaiful; Mahmudah, Qoniatul (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2022)
Marriage is a life process that is lived by humans and requires maturity and self-preparation from the husband and wife. To achieve the ideals of a peaceful and happy family, wisdom and responsibility are needed. Islam teaches the importance of cultivating intimate love and maintaining affection in the family. This article is focused on discussing the limitations of a wife's obedience to her husband in the view of Islam. While the purpose of this article is to explain the points or limitations of obedience that a wife needs to pay attention to in running the household, so that there is no discrimination against a wife. This is to support the creation of a sakinah mawaddah wa Rahmah family. The basic principle of building a sakinah mawaddah wa rahmah family in the view of Islam is choosing a life partner according to Islamic instructions. Then after entering the household gate, the husband and wife must fulfill their respective rights and obligations. If the rights and obligations are carried out correctly and sincerely, a sakinah mawaddah warahmah household will be established. The limitation of the wife's obedience to her husband in reaching the sakinah mawaddah warahmah household in the Islamic view is obedience in terms of goodness, not in disobedience.